Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.26630/jak.v9i1.2111
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Faktor yang Mempengaruhi Kejadian Demam Berdarah Dengue di Wilayah Kerja Puskesmas Way Kandis Bandar Lampung Tahun 2020

Abstract: <em>World Health Organization </em>(WHO) melaporkan bahwa terjadi peningkatan jumlah kasus DBD khususnya di negara tropis seperti Indonesia. Di Bandar Lampung terjadi instabilitas pada <em>Incidence Rate </em>(IR) dari tahun 2010-2015 dan Tanjung Senang merupakan wilayah dengan angka kasus tertinggi yaitu 138 kasus. Tujuan penelitian ini untuk mengetahui faktor yang mempengaruhi kejadian Demam Berdarah<em> Dengue</em> (DBD) di Wilayah Kerja Puskesmas Way Kandis Bandar Lampun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
(10 reference statements)
3
3
1
1
Order By: Relevance
“…This is because the layout of housing in urban and rural areas in Buleleng District is done well and is not in a slum condition hence there is a low risk of causing DHF. Our findings are not in line with the study conducted (Husna et al, 2020) which found that residents who have houses less than 40 meters away from other houses have a 2.5 times higher risk of DHF than residents whose houses are more than 40 meters apart another house building. Infectious disease studies also reported that crowded housing conditions and slums tended to be more susceptible to disease.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is because the layout of housing in urban and rural areas in Buleleng District is done well and is not in a slum condition hence there is a low risk of causing DHF. Our findings are not in line with the study conducted (Husna et al, 2020) which found that residents who have houses less than 40 meters away from other houses have a 2.5 times higher risk of DHF than residents whose houses are more than 40 meters apart another house building. Infectious disease studies also reported that crowded housing conditions and slums tended to be more susceptible to disease.…”
Section: Discussioncontrasting
confidence: 99%
“…DHF transmitting mosquitoes usually cannot breed in standing water that is in direct contact with the ground. Our findings are in line with the results of a study conducted (Husna et al, 2020) which found that open containers had a 1 times higher risk of causing DHF than water containers in closed conditions. The study conducted by (Gama and Betty, 2010) confirmed our findings that the number of containers above 3 units has a 6.75 times higher risk of causing the incidence of DHF compared to containers below or equal to 3 units.…”
Section: Discussionsupporting
confidence: 92%
“…Pantouw et al (2017) in their research conducted in Tuminting Sub-district showed that there was no significant effect on the eradication of Dengue Fever. Husna et al (2020) shows that knowledge has no effect on the incidence of dengue fever in the working area of the Way Kandis Public Health Center, Bandar Lampung. This study is also in line with Sholihah et al (2020) research conducted in Kupang City his research showed that there was no influence of knowledge on the incidence of Dengue Fever.…”
Section: Discussionmentioning
confidence: 99%
“…Areas with STBM villages cannot guarantee DHF-free zones since, in addition to sanitation, other factors such as the environment (availability of container lids, wire mesh availability, and space among houses) including community characteristics (education, work, and behavior) might influence the frequency of dengue fever (17).…”
Section: The Villages Adopting Community-based Total Sanitation In 20...mentioning
confidence: 99%